2012
DOI: 10.2118/140960-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Modification of the Dykstra-Parsons Method for Inclined Stratified Reservoirs

Abstract: The Dykstra-Parsons method (Dykstra and Parsons 1950) is used to predict the performance of waterflooding in noncommunicating stratified reservoirs. Much interest has been shown recently in the application of the method to chemical flooding, particularly for the case of polymer injection used for mobility control. The original method assumes that the reservoir layers are horizontal; however, most oil reservoirs exhibit a dip angle, with water being injected in the updip direction. Therefore, it is important to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The former is represented by the IV value; since a more uniform inflow rate distribution along the length of the completion will enhance the long-term objectives. (El-Khatib, 2012 showed that the breakthrough time, fractional recovery and water cut of a heterogeneous reservoir are all a function of the IV value for an OH well. )…”
Section: Figure 5-universal Type Curves Of Well Productivity Ratio (Pmentioning
confidence: 99%
“…The former is represented by the IV value; since a more uniform inflow rate distribution along the length of the completion will enhance the long-term objectives. (El-Khatib, 2012 showed that the breakthrough time, fractional recovery and water cut of a heterogeneous reservoir are all a function of the IV value for an OH well. )…”
Section: Figure 5-universal Type Curves Of Well Productivity Ratio (Pmentioning
confidence: 99%
“…Tian et al [26] studied the influence of strata pinch out and lens on vertical interlayer interference tests by establishing a three-layer model. Using the theory of B-L displacement mathematical model, Noaman et al [27][28][29] analyzed the influence of gravity number, mobility ratio, permeability variation coefficient and liquidity on waterflooding performance in inclined multilayer reservoirs, and compared the finding with the D-P method. Guo [30] established the low permeability gas reservoir model for multilayer commingling production, considering the Darcy flow and the starting pressure gradient in both cases.…”
Section: Introductionmentioning
confidence: 99%